Pengaruh Modifikasi Permainan Dakon Pintar Dengan Metode Penugasan Untuk Meningkatkan Keterampilan Numerasi Anak Usia 5-6 Tahun Di TK Darus Sholah Jember - Unshita Rini; Yulianti Fitriani; Erie Siti Syarah (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
This study aims to analyze the effect of the modified Dakon Pintar game integrated with an assignment method on the numeracy skills of children aged 5–6 years at Darus Sholah Kindergarten, Jember. The research employed a quasi-experimental approach using a nonequivalent control group design involving two groups: an experimental group (n=16) and a control group (n=16). Data were collected through numeracy skill tests (pretest and posttest). Data analysis used nonparametric statistics, including the Wilcoxon test and the Mann–Whitney test, complemented by N-Gain and effect size analysis. Results indicate that the experimental group showed significantly higher improvement than the control group. The Mann–Whitney test demonstrated a significant difference (p < 0.001), with the experimental group achieving a high N-Gain category while the control group fell within the low to moderate category. The effect size value of 0.85 indicates a very strong influence of the treatment. These findings suggest that the modified Dakon Pintar game combined with the assignment method is effective in enhancing early childhood numeracy skills through concrete experiences, increased engagement, and deeper conceptual understanding.